2019
DOI: 10.2147/ijn.s196651
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synergism of cisplatin-oleanolic acid co-loaded calcium carbonate nanoparticles on hepatocellular carcinoma cells for enhanced apoptosis and reduced hepatotoxicity</p>

Abstract: Background: Cisplatin (CDDP), a widely used chemotherapeutic agent against hepatocellular carcinoma (HCC), faces severe resistance and hepatotoxicity problems which can be alleviated through combination therapy. Purpose: The objective of this study was to develop a pH-dependent calcium carbonate nano-delivery system for the combination therapy of CDDP with oleanolic acid (OA). Methods: A microemulsion method was employed to generate lipid coated cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 61 publications
6
43
0
Order By: Relevance
“…The content of OA was measured by high-performance liquid chromatography (LC-2030, Shimadzu, Japan) with the following conditions: Agilent SB-C18 880975-902 column (4.6 mm, 250 mm, 5 mm); mobile phase was 0.1% TFA aqueous solution: acetonitrile/methanol mixture (17:1) ¼1:9. The temperature is 30 C, the flow rate was 1 mL/min and the detection wavelength was 210 nm (Khan et al, 2019).…”
Section: Drug Loading and Drug Releasementioning
confidence: 99%
“…The content of OA was measured by high-performance liquid chromatography (LC-2030, Shimadzu, Japan) with the following conditions: Agilent SB-C18 880975-902 column (4.6 mm, 250 mm, 5 mm); mobile phase was 0.1% TFA aqueous solution: acetonitrile/methanol mixture (17:1) ¼1:9. The temperature is 30 C, the flow rate was 1 mL/min and the detection wavelength was 210 nm (Khan et al, 2019).…”
Section: Drug Loading and Drug Releasementioning
confidence: 99%
“…Hepatotoxicity is also considered as one of the most frequent adverse effects of platinum-based compounds administration in clinical practice. Morphological alterations accompanying platinum-based compounds application are manifested as necrosis, degeneration of hepatocytes, and increased inflammatory response [ 19 ], as well as a consequent increase in hepatic enzymes and bilirubin [ 20 ]. Long-term survival analysis of platinum-based compounds-induced hepatotoxicity showed that liver damage was more pronounced following cisplatin administration when compared to carboplatin [ 21 ], while drug-induced hepatotoxicity manifestations accompanying oxaliplatin therapy were predominantly restricted to hepatic vascular injury [ 22 ].…”
Section: Side Effects Of Platinum-based Compounds In Clinical Pracmentioning
confidence: 99%
“…However, considering the side effects and resistance of antineoplastic drugs of HCC treatment, some new extracts from common plants can directly antagonize HCC growth, improve the anticancer activity, and reduce hepatotoxicity by enhancing p53 function and disrupting MDM2-p53 interaction. Oleanolic acid can help cisplatin to overcome the chemotherapeutic resistance by activating p53/Bax/ cytochrome C/caspase-3 proapoptotic signaling pathway 155 . Acetylshikonin can directly promote HepG2 cell apoptosis by activating p53/PUMA/Bax pathway 156 .…”
Section: Anti-hcc By Restoring P53 Function and Normalizing Mdm2-p53 mentioning
confidence: 99%